Revisão sistemática de soluções tecnológicas e organizacionais para conformidade com a LGPD - Belarmino, Gabriel da Silva (2024)
The brazilian General Data Protection Law (Law No. 13,709, of August 14, 2018) governs the processing of personal data and describes new sociotechnical challenges and demands to modernize the legal system, as well as to promote advances in Data Governance and Information Security. Its objective is to expand citizens’ fundamental rights and establish new principles and guidelines for developing an organizational culture capable of ensuring data protection. Compliance with LGPD requires several changes, not only in legalfocused regulations and business policies, but also in practical and technical issues related to work processes, technological infrastructure, and data management, which are the focus of this study. This paper conducts a systematic literature review on personal data protection to identify compliance solutions. It presents technological artifacts related to system implementation and organizational management, preparing internal processes to meet security requirements, reduce privacy risks, and comply with LGPD demands. The review explored 41 qualified studies, describing relevant solutions for research. Based on these results, 14 recommendations were proposed to assist organizations in their LGPD compliance process. Additionally, recommendations were made regarding data protection documentation and prioritized requirements for legislative compliance.